Multifunctional two-dimensional semiconductors SnP3: universal mechanism of layer-dependent electronic phase transition. (31st October 2018) - Gong, Peng-Lai; Zhang, Fang; Huang, Liang-Feng; Zhang, Hu; Li, Liang; Xiao, Rui-Chun; Deng, Bei; Pan, Hui; Shi, Xing-Qiang
Abstract: Two-dimensional (2D) semiconductors SnP3 are predicted, from first-principles calculations, to host moderate band gaps (0.72 eV for monolayer and 1.07 eV for bilayer), ultrahigh carrier mobility (̃10 4 cm 2 V −1 s −1 for bilayer), strong absorption coefficients (̃10 5 cm −1 ) and good stability. Moreover, the band gap can be modulated from an indirect character into a direct one via strain engineering. For experimental accessibility, the calculated exfoliation energies of monolayer and bilayer SnP3 are smaller than those of the common arsenic-type honeycomb structures GeP3 and InP3 . More importantly, a semiconductor-to-metal transition is discovered with the layer number N   >  2. We demonstrate, in remarkable contrast to the previous understandings, that such phase transition is largely driven by the correlation between lone-pair electrons of interlayer Sn and P atoms. This mechanism is universal for analogues phase transitions in arsenic-type honeycomb structures (GeP3, InP3 and SnP3 ).